2011
DOI: 10.1021/nn204012y
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Assemblies and Densest Packings of a Family of Truncated Tetrahedra and the Role of Directional Entropic Forces

Abstract: Polyhedra and their arrangements have intrigued humankind since the ancient Greeks and are today important motifs in condensed matter, with application to many classes of liquids and solids. Yet, little is known about the thermodynamically stable phases of polyhedrally shaped building blocks, such as faceted nanoparticles and colloids. Although hard particles are known to organize due to entropy alone, and some unusual phases are reported in the literature, the role of entropic forces in connection with polyhe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
280
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 213 publications
(296 citation statements)
references
References 34 publications
15
280
0
1
Order By: Relevance
“…As previously mentioned, similar approaches have been applied for tetrahedra 65,90 and truncated tetrahedra. 68,91 However, it is also possible that the numerical results are of sufficient quality to "guess" the analytic solutions which maximizes the density and verify that this structure does not give overlaps using an analytic form of our overlap techniques. We used this approach for rhombicuboctahedra and rhombic enneacontrahedra in Ref.…”
Section: Close-packed Crystal Structures For Anisotropic Particlesmentioning
confidence: 95%
See 4 more Smart Citations
“…As previously mentioned, similar approaches have been applied for tetrahedra 65,90 and truncated tetrahedra. 68,91 However, it is also possible that the numerical results are of sufficient quality to "guess" the analytic solutions which maximizes the density and verify that this structure does not give overlaps using an analytic form of our overlap techniques. We used this approach for rhombicuboctahedra and rhombic enneacontrahedra in Ref.…”
Section: Close-packed Crystal Structures For Anisotropic Particlesmentioning
confidence: 95%
“…For the truncated tetrahedra, we discovered a new crystal structure which improved upon the literature value of the densest packing. Subsequent numerical and analytic studies 68,91 showed that this value could be further improved upon.…”
Section: Close-packed Crystal Structures For Anisotropic Particlesmentioning
confidence: 98%
See 3 more Smart Citations